A Movie with the Structure of Byzantine Liturgy: Megalexandros by Theo Angelopoulos - Seppälä, Serafim (Journal of the International Society for Orthodox Music, 2020)
The most important Greek film director of all times, Theo Angelopoulos is known for his leftist and humanist themes, but he was also influenced and inspired by the aesthetics of the Orthodox Church. In particular, Megalexandros (1980) is full of Orthodox and Byzantine ingredients. A three and half hour epic full of obscure symbolism from different layers of time, the film has proven to be a difficult case for interpreters and analysts. According to Angelopoulos himself, Megalexandros was “structured like a Byzantine liturgy”. In spite of the plentiful academic research on his work, the idea has not been properly analysed, even though it provides a suitable key to the many oddities of the film. The structure of Byzantine liturgy functions in the film on three levels. Firstly, the visual settings of scenes contain explicit and obvious iconic settings of baptism, Eucharist and Saint George, in addition to more obscure ones such as entry to Jerusalem and some iconic posing in other scenes. Moreover, the visual sceneries contain cases of symbolic movement that appears ritualistic and creates a sense of sacredness. Secondly, the usage of soundscape has parallels with the Byzantine liturgical singing, albeit it consists mainly of religious folk songs rather than actual liturgical hymns. The effects and impressions created by music resemble those of liturgical singing, however, and in that sense, the movie constitutes a wider secular application of liturgical principles. The arrangement aptly shows how the ecclesiastical spirit was at the heart of traditional Greek village culture. Moreover, there is one liturgical hymn, Troparion of the Cross, which seems to function as a symbol of the collective will to power. Thirdly, and most importantly, the structural elements of the narrative function “liturgically” in a phenomenological sense: they create turns, shifts and moods that are parallel with the contents of mind when one is present in Byzantine liturgical settings. In particular, the central figure, Alexander, does not direct his community by decisions or conversations, or by showing his emotions, but rather leads it by his presence and authority – very much like a bishop leads liturgical worship in the Byzantine cult. In the film, this phenomenology of liturgy applies to explicit visual elements of the narrative on the one hand, and on their reception on the other. The result is something that may look mysterious or inexplicable but feels like Byzantine liturgy.